RESIDENTS’ CHANGE IN SOCIALIZATION AND LONELINESS SINCE MOVING TO SENIOR HOUSING - Taylor, H. (Innov Aging, 2017)
It is frequently assumed older adults who move to senior housing communities (SHCs) will socialize more and be less lonely. The purpose of this study is to describe changes in residents’ frequency of socialization and loneliness since moving into senior housing, and to determine factors associated with these changes. Ninety-six older adults living in two SHCs completed cross-sectional surveys with items regarding changes in socialization and loneliness since moving into a SHC, age, education, depressive symptoms, anxiety symptoms, years lived in the SHC, and distance to previous residence. Analyses for the current study include descriptive statistics and multinomial logistic regression models. Since moving into a SHC, twenty-five percent of residents had decreases in socializing with family, 20% had decreases in socializing with friends, 19% had decreases in level of companionship, 21% felt more left out, and 14% felt more isolated. Age, education, anxiety symptoms, and years living in the SHC were related to changes in socialization and loneliness in the multinomial logistic models. These analyses suggest a significant portion of older adults living in senior housing may socialize with friends and family less and feel lonelier after moving to senior housing. It is important to understand the reasons for decreasing social interactions and increasing loneliness after older residents move to senior housing, and how to intervene upon their behalf. Additional studies are needed to determine if these findings are consistent, and interventions should be developed to increase socializing and decrease loneliness among residents living in senior housing.